2017
DOI: 10.1186/s13104-017-2774-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the practice of exclusive breastfeeding among nursing mothers in a peri-urban district of Ghana

Abstract: BackgroundExclusive breastfeeding (EBF) is one of the optimal infant and young child feeding practices. Globally, <40% of infants under 6 months of age are exclusively breastfed. In Ghana, 63% of children <6 months are exclusively breastfed which is far less than the 100% recommended by the United Nation Children Emergency Fund. This study was carried out to find out the factors that influence the practice of exclusive breastfeeding in the district.MethodsA cross-sectional quantitative study was conducted usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
32
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 4 publications
9
32
2
7
Order By: Relevance
“…The findings showed that, mothers who were selfemployed artisans were more likely to practice exclusive breastfeeding. This finding was in line with earlier studies that found self-employed mothers to be more likely to practice 6 months exclusive breastfeeding [43]. This study found that mothers whose households were headed by males were more likely to practice exclusive breastfeeding but this relationship was not statistically significant after adjusting for other explanatory variables.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings showed that, mothers who were selfemployed artisans were more likely to practice exclusive breastfeeding. This finding was in line with earlier studies that found self-employed mothers to be more likely to practice 6 months exclusive breastfeeding [43]. This study found that mothers whose households were headed by males were more likely to practice exclusive breastfeeding but this relationship was not statistically significant after adjusting for other explanatory variables.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that mothers whose households were headed by males were more likely to practice exclusive breastfeeding but this relationship was not statistically significant after adjusting for other explanatory variables. This result was similar to the findings of other studies in Ghana [43] and Malawi [44] where the decision of 6 months and 24 to 26 h exclusive breastfeeding was influenced by spouses and family members respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The findings show that, mothers who are self-employed artisans are more likely to practice exclusive breastfeeding. This finding is in line with earlier studies that found self-employed mothers to be more likely to practice exclusive breastfeeding [43]. This study found that mothers whose households were headed by males were more likely to practice exclusive breastfeeding but this relationship is not statistically significant after adjusting for other explanatory variables.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that mothers whose households were headed by males were more likely to practice exclusive breastfeeding but this relationship is not statistically significant after adjusting for other explanatory variables. This result is similar to the findings of other studies in Ghana [43] and Malawi [44] where the decision of exclusive breastfeeding is influenced by spouses and family members.…”
Section: Discussionsupporting
confidence: 91%
“…As to the maternal physical condition and psychological mood, the factors of anemia and throat infection were illustrated without significant variation. Similarly, uses of unauthorized oral antibiotics and negative emotion were not associated with mastitis that was opposite to the views reported in other literatures [16,17]. Contact with infant after birth within 1 h accounted for a greater proportion in control group and protect women from mastitis (OR = 0.565, 95%CI = 0.340-0.938).…”
Section: Univariate Analysis and Multivariate Logistic Regression Anacontrasting
confidence: 83%